Analysis and Experiment Method of Influence of Retaining Sleeve Structures and Materials on Rotor Eddy Current Loss in High-Speed PM Motors - Han, Ting; Wang, Yunchong; Shen, Jian-Xin (IEEE transactions on industry applications, 2020)
A rotor retaining sleeve is usually essential in high-speed permanent magnet (PM) motors to firmly retain the magnets and ensure the rotor integrity. The structure and material of retaining sleeve have a significant effect on rotor losses, especially on the rotor eddy current loss. On the other hand, heat dissipation from the rotor is difficult, therefore, any excessive rotor loss may lead to over temperature and cause irreversible demagnetization of the magnets. In this article, the influence of retaining sleeve with different structures and materials on the rotor eddy current loss in high-speed PM motors will be comprehensively investigated, with both 3-D finite element method simulations and experiments. Particularly, the proposed experiments are carried out with a stationary rotor. The study reveals that the equivalent conductivity of the retaining sleeve has a significant influence on the rotor eddy current loss, and countermeasures can be made accordingly so as to reduce the rotor eddy current loss.